2020
DOI: 10.1017/s095026882000237x
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the epidemiological trends of COVID-19 prevalence and mortality using the advanced α-Sutte Indicator

Abstract: Forecasting the epidemics of the diseases is very valuable in planning and supplying resources effectively. This study aims to estimate the epidemiological trends of the coronavirus disease 2019 (COVID-19) prevalence and mortality using the advanced α-Sutte Indicator, and its prediction accuracy level was compared with the most frequently adopted autoregressive integrated moving average (ARIMA) method. Time-series analysis was performed based on the total confirmed cases and deaths of COVID-19 in the world, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…Given the forecasting superiority of our proposed data-driven hybrid method, it seems that this hybrid model is also useful in nowcasting and forecasting the epidemiological trends of the COVID-19 prevalence and mortality time series in other regions or other infectious diseases 44 . Of note, current studies found that some other forecasting tools (e.g., the new innovations state space modeling framework 59 , long short-term memory neural network 60 , advanced error-trend-seasonal (ETS) framework 61 , α-Sutte Indicator 62 , and SBDiEM 30 ) performed a highly accurate forecast for the epidemiological trends of COVID-19. As a result, to further our research we are planning to make a comparative study between our proposed EEMD-SARIMA-NARANN hybrid model and the ones above.…”
Section: Discussionmentioning
confidence: 99%
“…Given the forecasting superiority of our proposed data-driven hybrid method, it seems that this hybrid model is also useful in nowcasting and forecasting the epidemiological trends of the COVID-19 prevalence and mortality time series in other regions or other infectious diseases 44 . Of note, current studies found that some other forecasting tools (e.g., the new innovations state space modeling framework 59 , long short-term memory neural network 60 , advanced error-trend-seasonal (ETS) framework 61 , α-Sutte Indicator 62 , and SBDiEM 30 ) performed a highly accurate forecast for the epidemiological trends of COVID-19. As a result, to further our research we are planning to make a comparative study between our proposed EEMD-SARIMA-NARANN hybrid model and the ones above.…”
Section: Discussionmentioning
confidence: 99%
“…The ARIMA method is introduced to make a forecast by mining the intrinsical attributes and inherent rules of time series data. 31 HFRS frequently has notable seasonal effects, 2 , 10 and hence the seasonal ARIMA (SARIMA) method should be adopted. In this method, the seasonality of HFRS was thought of as the predictors and the monthly HFRS incidence as the response variable.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, time series is characterized by noticeable correlations between successive observed values. 32 The most classical approach to consider the association patterns of a time series is the ARIMA model. 29 Since the incidence series of infectious diseases often shows marked seasonal variation and periodicity, and thus the seasonal ARIMA (SARIMA) is more appropriate for capturing the dynamic dependence structure in the HFMD incidence.…”
Section: Sarima Modelmentioning
confidence: 99%